Does a genius produce his artworks like an apple tree, its apples? - Figueiredo, Virginia (Con-Textos Kantianos. International Journal of Philosophy, 2022)
This article addresses two issues: the first is the philosopher's fear of a lawless freedom of nature. I quote Deleuze and Guattari, who explain our terror before chaos and the consequent call for help and protection. My hypothesis was that this threat of chaos has affected also the enlightened mind of Kant. Facing the possibility of chaos, the objective Kant did not exactly fear delusion and madness, which affect only fragile subjectivities, but was terrified with the chance that nature does not behave regularly, i.e., that knowledge becomes impossible. The second issue is a harder and more difficult question, and it is related to the modern artist’s (or genius) anguish. It is a technical or an artistical complaint. He/She finds no more given rules to create his/her artworks. Differently from the philosopher, the genius fears the silence and the absolute muteness of nature. I try to deal with these two issues by taking into account Kant’s concept of purposiveness of nature as a regulative principle. I realize that, although this sufficed to calm down the philosopher’s anxiety, it proved to be insufficient to guide the artist. The delusion and madness that threaten the genius are deeper and more extreme than those of the philosopher. In order to treat the artist’s pain, without having to abandon the connection between art and nature, that constitutes one of the most fruitful reading keys of Kant’s Aesthetics, I resort to other ideas I found reading Lacoue-Labarthe and Hannah Arendt.
Keywords: Kant; Theory of Genius; Critique of Power of Judgment; art and nature